Adaptasi dan Pengujian Alat Ukur Brain Fog Scale (BFS) pada Mahasiswa di Indonesia - Nona Khairunnisa Mumtaz; Fatima Mansoor; Firdausyi Azahrani; Nandya Tabina Arnita; Diah Zaleha Wyandini; Ghinaya Ummul Mukminin Hidayat (Humanitas (Jurnal Psikologi), 2025)
This study aims to adapt the Brain Fog Scale (BFS) measurement tool for the young adult population in Indonesia. Brain fog is a cognitive disorder characterized by difficulties in concentration, confusion, and mental fatigue. Although many reports describe the symptoms of brain fog, systematic tools for detecting and evaluating this condition are still limited. This research employs a quantitative method with psychometric analysis, including validity and reliability testing. The sample consisted of 208 students selected using convenience sampling. Data were collected using the BFS questionnaire, which consists of 23 items covering three dimensions: mental fatigue, impaired cognitive acuity, and confusion. Data analysis was conducted using Confirmatory Factor Analysis (CFA) for construct validity testing and alpha coefficients for reliability testing. The results show high reliability (alpha = 0.935); however, the construct validity test revealed that the model did not fully fit, with Chi-Square, CFI, and RMSEA values not meeting model fit criteria, although the SRMR value indicated good results. These findings suggest that the BFS tool requires revision to improve construct validity, especially in the Indonesian cultural context. This study provides a foundation for the development of a more suitable BFS tool for detecting brain fog symptoms in young adult individuals.